2004
DOI: 10.1097/00002030-200401230-00011
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of treatment interruption in HIV-infected patients with multiple therapeutic failures

Abstract: Treatment interruption was beneficial for treatment-experienced HIV-infected patients with advanced HIV disease and multidrug-resistant virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 29 publications
2
54
5
Order By: Relevance
“…Other options such as complete or partial structured treatment interruptions have failed to show consistent benefit or not undergone careful scrutiny in clinical trials. [22][23][24] Complicating these decisions is the relative paucity of data regarding the rate at which anti-retroviral resistance develops after the onset of virologic treatment failure in patients receiving highly active anti-retroviral therapy (HAART). [25][26][27] The purpose of this study was to define the time to accrual of genotypic resistance mutations, particularly thymidine analogue mutations (TAMs) and major protease inhibitor mutations, in persons with a persistently detectable plasma viral load (pVL) despite being on a stable antiretroviral regimen.…”
mentioning
confidence: 99%
“…Other options such as complete or partial structured treatment interruptions have failed to show consistent benefit or not undergone careful scrutiny in clinical trials. [22][23][24] Complicating these decisions is the relative paucity of data regarding the rate at which anti-retroviral resistance develops after the onset of virologic treatment failure in patients receiving highly active anti-retroviral therapy (HAART). [25][26][27] The purpose of this study was to define the time to accrual of genotypic resistance mutations, particularly thymidine analogue mutations (TAMs) and major protease inhibitor mutations, in persons with a persistently detectable plasma viral load (pVL) despite being on a stable antiretroviral regimen.…”
mentioning
confidence: 99%
“…It has been reported that the use of boosted protease inhibitors (Boosted PI) is associated with multiple clinical benefits, including higher efficacy against resistant HIV strains [28], lower rates of resistance emergence at highadherence levels [29] and a lack of PI-associated resistance mutations after virologic failure in treatment-naïve patients [30]. As well, studies have shown that Boosted PI offers a marginal independent protective effect on disease progression [23,31]. As the prevalence of HIV drug resistance accumulates in China, the need for scaling up second-line therapy is clear and must be a priority in China's efforts to control HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Both non-adaptive and adaptive STI strategies have been studied in individuals with chronic infection (Katlama et al, 2004;Lawrence et al, 2003;Ruiz et al, 2000;Ruiz et al, 2003;El-Sadr and Neaton, 2006), based on several rationales for interrupting therapy in these patients (Hirschel, 2001). One is to provide "drug holidays," breaks from the burden and side effects of antiretroviral therapy (while hopefully not negating the benefits).…”
Section: Hiv Therapy and Structured Or Supervised Treatment Interruptionmentioning
confidence: 99%
“…These observations have led to the hypothesis that an interruption in therapy eliminates drug pressure, resulting in reversion of viral populations to a more susceptible viral quasi-species, thus improving chances that subsequent salvage regimens will be effective. Although studies have demonstrated that virus harboring genotypic mutations can revert back to wild-type quasi-species and may improve virologic outcome (Katlama et al, 2004), clinical benefit of treatment interruption in chronically-infected patients leads has not been established (Antinori et al, 2005;Ghosn et al, 2005;Yeni et al, 2004).…”
Section: Hiv Therapy and Structured Or Supervised Treatment Interruptionmentioning
confidence: 99%